Exchange Rate Policy in Developing Countries : Some Analytical Issues - Montiel, Peter; Aghevli, Bijan; Khan, Mohsin (Washington, D.C. : International Monetary Fund, 1991)
This paper addresses analytical aspects of exchange rate policy and emphasizes the relationship among exchange rate flexibility, financial discipline, and international competitiveness.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet